Health Education And Disaster Relief Empowerment Pemuda Reaktif Tanggap Bencana (Pereda Bencana) In Youth SMP Negeri 2 Martapura Timur Banjar Regency, South Kalimantan - Istiana; Vina Yulia Anhar; Ihya Hazairin Noor; Zuhrufa Wanna Yolanda; Husnul Fatimah; Agus Muhammad Ridwan; Farid Ilham Muddin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
In 2021 based on data from the South Kalimantan Regional Disaster Management Agency , there have been floods that hit 11 districts/cities in South Kalimantan , in where floods causecommunity activities to be completely paralyzed. Banjar Regency is the district with the second most flooding with a total of 32 flood disasters in the Regency area. Flood disasters occurred in 15 sub -districts and recorded as many as 275,906 souls and 22,967 houses were affected , while 27 . 440 people evacuated i. Disaster knowledge is needed by the community, especially teenagers, because teenagers play an important role in understanding this context and can reduce the risk and danger of flood disasters. One of the solutions formulated is to conduct counseling on disaster mitigation which is packaged in the Reactive Youth and Disaster Response (PEREDA DISASTER) program for students at SMPN 2 Martapura Timur, BanjarRegency . To increase knowledge and information for students of SMPN 2 Martapura Timur regarding flood disasters and Disaster Risk Reduction (DRR). This research is a descriptive research . The method used by the community service team is through health education in the form of counseling with the aim of increasing adolescent understanding and preparedness for flood disasters with communicative activities . The implementation of this community service is carried out through several stages . namely site surveys and situation analysis, licensing, equalization of perceptions, preparation of materials and instruments, finalization of targets, coordination of activities, implementation of counseling and demonstrations, evaluation of knowledge improvement and reporting. Based on the analysis, some students experienced an increase in the post-test, to be precise as many as 37 students experienced an increase, 23 students did not experience a decrease or increase, and 5 students experienced a decrease. Health education and the formation of disaster-responsive reactive youth (PEREDA DISASTER) can increase students' knowledge as seen from the results of research which states that respondents already know about floods, their causes, impacts, diseases that often occur and steps that must be taken during and after floods.